On the Symmetry, Electronic Properties, and Possible Metallic States in NASICON-Structured A4V2(PO4)3 (A = Li, Na, K) Phosphates - Gryaznov, Denis; Vilčiauskas, Linas (My University, 2023)
In this work, the electronic structure and properties of NASICON-structured A4V2(PO4)3, where A = Li, Na, K were studied using hybrid density functional theory calculations. The symmetries were analyzed using a group theoretical approach, and the band structures were examined by the atom and orbital projected density of states analyses. Li4V2(PO4)3 and Na4V2(PO4)3 adopted monoclinic structures with the (Formula presented.) space group and averaged vanadium oxidation states of V (Formula presented.) in the ground state, whereas K4V2(PO4)3 adopted a monoclinic structure with the (Formula presented.) space group and mixed vanadium oxidation states V (Formula presented.) /V (Formula presented.) in the ground state. The mixed oxidation state is the least stable state in Na4V2(PO4)3 and Li4V2(PO4)3. Symmetry increases in Li4V2(PO4)3 and Na4V2(PO4)3 led to the appearance of a metallic state that was independent of the vanadium oxidation states (except for the averaged oxidation state (Formula presented.) Na4V2(PO4)3). On the other hand, K4V2(PO4)3 retained a small band gap in all studied configurations. These results might provide valuable guidance for crystallography and electronic structure investigations for this important class of materials. © 2023 by the authors. --//-- Gryaznov D., Vilčiauskas L.; On the Symmetry, Electronic Properties, and Possible Metallic States in NASICON-Structured A4V2(PO4)3 (A = Li, Na, K) Phosphates; (2023) Materials, 16 (12), art. no. 4361; DOI: 10.3390/ma16124361; https://www.scopus.com/inward/record.uri?eid=2-s2.0-85164166600&doi=10.3390%2fma16124361&partnerID=40&md5=f3050838dc58f36c6ffbf7f7d4195700. Published under the CC BY 4.0 licence.
This project has received funding from the European Regional Development Fund (Project No. 01.2.2-LMT-K-718-02-0005) under grant agreement with the Research Council of Lithuania (LMTLT). The Institute of Solid State Physics through the University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; density functional theory; hybrid-exchange-correlation functionals; NASICON; sodium vanadium phopshate